2018
DOI: 10.1101/468900
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Previewing a face in the periphery reduces the fN170: Combined EEG and eye-tracking suggests two stages of trans-saccadic predictive processes

Abstract: The world appears stable despite saccadic eye-movements. One possible explanation for this phenomenon is that the visual system predicts upcoming input across saccadic eye-movements, based on peripheral preview of the saccadic target. We tested this idea using concurrent electroencephalography (EEG) and eye-tracking. Participants made cued saccades to peripheral upright or inverted face stimuli that could change (invalid preview) or keep their orientation (valid preview) across the saccade. Experiment 1 demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 95 publications
2
1
0
Order By: Relevance
“…In other words, while ERP researcher have traditionally presented isolated objects during steady fixation, visual objects are typically primed and/or predicted during natural vision based on a coarse extrafoveal preview of the object. Indeed, a similar preview effect, as shown here for words, was recently reported for the N170 component of previewed human faces (Buonocore, Dimigen, & Melcher, 2020;de Lissa et al, 2019;Huber-Huber et al, 2018). This indicates that the attenuation of the late N1 and N170 components by preview may be a characteristic feature of visual object recognition under real-world conditions.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In other words, while ERP researcher have traditionally presented isolated objects during steady fixation, visual objects are typically primed and/or predicted during natural vision based on a coarse extrafoveal preview of the object. Indeed, a similar preview effect, as shown here for words, was recently reported for the N170 component of previewed human faces (Buonocore, Dimigen, & Melcher, 2020;de Lissa et al, 2019;Huber-Huber et al, 2018). This indicates that the attenuation of the late N1 and N170 components by preview may be a characteristic feature of visual object recognition under real-world conditions.…”
Section: Discussionsupporting
confidence: 88%
“…The first reason is of methodological nature and directly linked to the problems of overlap and covariates: The baseline for the FRP is often biased because of differences in the duration of the preceding fixation, differences in the size of the preceding saccade, or a different overlap with the stimulus-onset ERP. Several workarounds have been proposed to deal with this problem, such as placing the baseline before trial onset (Dimigen et al, 2011;Nikolaev et al, 2016) before an earlier fixation (Coco et al, 2018;Degno et al, 2018, Huber-Huber et al, 2018, or in the first few milliseconds after fixation onset ( However, a second reason why the baseline should still be chosen carefully are effects of preprocessing. Because viewers obtain some information about soon-to-be fixated items in parafoveal and peripheral vision (Baccino & Manunta, 2005;Buonocore et al, 2020;Coco et al, 2018;de Lissa et al, 2019), EEG effects may in some cases already begin before an object is foveated (e.g.…”
Section: Baseline Correction and Placementmentioning
confidence: 99%
“…Evidence from experiments with human subjects point in the same direction, although the effects are only observed after saccade offset (but this could be due to methodological constraints). Multiple fMRI studies (Dunkley et al, 2016;Fairhall et al, 2017;Merriam et al, 2003;Zimmermann, Weidner, et al, 2016) and EEG studies (Edwards et al, 2018;Huber-Huber, Buonocore, Hickey, & Melcher, 2018) showed that a visual stimulus before a saccade affects the processing of a stimulus at the same spatiotopic location after the saccade, corroborating observations from human psychophysics. Although these studies do show clear post-saccadic effects of a pre-saccadic stimulus, it remains unclear when these effects arise in the human visual system.…”
Section: Introductionsupporting
confidence: 61%